A Magnetorheological Elastomer‐Based Proportional Valve for Soft Pneumatic Actuators. (17th October 2022) - Wang, Sihan; He, Liang; Albini, Alessandro; Zhang, Peizhi; Maiolino, Perla
Abstract : The interest in soft pneumatic actuators has been growing rapidly in robotics, owing to the contact adaptability with the material softness. However, these actuators are mostly controlled by rigid electronic pneumatic valves, which can hardly be integrated into the robot itself, limiting its mobility and adaptability. Recent advances in soft or electronics‐free valve designs provide the potential to achieve an integrated soft robotic system with reduced weight and rigidity. Nevertheless, the challenge in valve response remains open. To enable dynamic control of a soft pneumatic actuator (SPA), a fast‐response proportional valve is needed. Herein, the potential of Ecoflex‐based magnetorheological elastomer (MRE) membrane to create a proportional valve that can be used in the control of a soft robot made from the same silicone material is explored. Experimental characterization shows that the proposed MRE valve (30 mm × 30 mm × 15 mm, 30 grams) can hold pressure up to 41.3 kPa and regulate the airflow in an analog manner. The valve is used to perform closed‐loop proportional–integral–differential (PID) control with 50 Hz on a SPA and is able to control the pressure within the actuator chamber with a root‐mean‐square error of 0.05 kPa. Abstract : Magnetorheological elastomer (MRE) proportional valves for controlling pneumatic soft robots are presented. The valves make use of the electromagnets to deform MRE membranes and regulate the flowrate or pressure of soft pneumatic robots in an analog manner. These proportional valves offer great potential to simplify the way soft pneumatic robots are controlled.